Resveratrol Promotes Nerve Regeneration via Activation of p300 Acetyltransferase-Mediated VEGF Signaling in a Rat Model of Sciatic Nerve Crush Injury - Ding, Zhuofeng; Cao, Jiawei; Shen, Yu; Zou, Yu; Yang, Xin; Zhou, Wen; Guo, Qulian; Huang, Changsheng (Frontiers in Neuroscience, 2018)
Peripheral nerve injuries are generally associated with incomplete restoration of motor function. The slow rate of nerve regeneration after injury may account for this. Although many benefits of resveratrol have been shown in the nervous system, it is not clear whether resveratrol could promote fast nerve regeneration and motor repair after peripheral nerve injury. This study showed that the motor deficits caused by sciatic nerve crush injury were alleviated by daily systematic resveratrol treatment within 10 days. Resveratrol increased the number of axons in the distal part of the injured nerve, indicating enhanced nerve regeneration. In the affected ventral spinal cord, resveratrol enhanced the expression of several vascular endothelial growth factor family proteins (VEGFs) and increased the phosphorylation of p300 through Akt signaling, indicating activation of p300 acetyltransferase. Inactivation of p300 acetyltransferase reversed the resveratrol-induced expression of VEGFs and motor repair in rats that had undergone sciatic nerve crush injury. The above results indicated that daily systematic resveratrol treatment promoted nerve regeneration and led to rapid motor repair. Resveratrol activated p300 acetyltransferase-mediated VEGF signaling in the affected ventral spinal cord, which may have thus contributed to the acceleration of nerve regeneration and motor repair.